Human papilloma virus DNA presence in early stage cervical carcinomas: Correlation with other prognostic factors and recurrence rate - Basheska, Neli; Ivkovski, Ljube; Yashar, Genghis; Stavrik, George (Gustav Fischer, 1997)
BACKGROUND: Although the role of human papillomavirus (HPV) in cervical carcinogenesis is reasonably well established, the attempts to determine the prognostic value of presence or absence of detectable human papillomavirus DNA and HPV type in cervical carcinoma have yielded conflicting results. OBJECTIVE: The objective of our study was to assess the prognostic significance of the presence of HPV DNA by exploring the relationship of HPV presence to the recurrence rate and clinical and histopathologic features of 92 patients with cervical carcinoma..In this report the preliminary results of a larger programme aimed to search for the prognostic factors in a fairly homogenous population of patients with early stage cervical carcinomas who underwent abdominal hysterectomy with pelvic lymphadenectomy as primary therapy, followed by postoperative adjuvant pelvic radiotherapy, are presented MATERIALS AND METHODS: Routinely processed formalin-fixed paraffin-embedded cervical carcinoma surgical specimens were examined for the presence of HPV DNA by in situ hybridization technique using mixed biotinylated probes to identify HPV types 6/11, 16/18 and 31/33/51 (Enzo Diagnostics, New York). Clinical data and histopathologic features of these patients were analyzed retrospectively to determine their relation to presence or absence of HPV DNA. All the patients were staged according to the postoperative TNM classification of UICC (1987) guidelines. In our case series the tumor was limited to cervix in 48 (52.2%) patients, while local extension to vagina and parametrial tissues was found in 10 (10.9%) and 34 (36.9%) patients, respectively. Pelvic lymph node involvement was found in 25 (27.2%) patients. During the follow-up period (range, 2-87, mean, 35 months), recurrences were observed in 13 patients. Variables were compared by cross-classification and statistical significance was determined by χ2 and Fisher`s exact test. RESULTS: HPV DNA was detected in 41 (44.6%) cervical carcinoma specimens. The prevalence rate of different HPV types was 37% (34) for HPV 16/18, 6.5% (6) for HPV 31/33/5, while HPV type 6/11 was detected only in one case of verrucous carcinoma. Recurrence rate was significantly higher in patients with HPV DNA negative cervical carcinomas (P=0.02). Among the HPV DNA positive patients with cervical carcinoma the recurrence rate was 4.9% (2 cases), compared to 21.6% (5 cases) for the HPV DNA negative group. Various clinical and histopathologic features of the patients with cervical carcinomas (tumor extent, grade, presence of regional lymph nodal metastases, number of positive lymph nodes, histologic subtype, maximum depth of cervical stromal invasion, maximal tumor diameter, longitudinal endocervical involvement, proportionate longitudinal endocervical involvement, tumor-cervix area quotient, maximal and minimal sagittal tumor area, parametrial involvement, vaginal involvement, lymph-vascular space invasion, peri- and intra-tumoral lymphocytic infiltration, surgical margins involvement, age) were also correlated with the presence of HPV DNA. No statistically significant association was found between the presence of HPV DNA and 17 other clinical and histopathologic variables. On the other hand recurrence rates were significantly related to tumor extent (P=0.0001), presence of regional lymph nodal metastases (P=0.0002), maximal tumor diameter (P=0.14), proportionate longitudinal endocervical involvement (P=0.007), maximal sagittal tumor area (P=0.038), parametrial involvement (P=0.0001), vaginal involvement (P=0.03), and lymph-vascular space invasion (P=0.0023). CONCLUSIONS: The preliminary results of our study are consistent the observations reported by several other authors. The presence of HPV DNA appeared to be related to recurrence rate and unrelated to various histopathologic characteristics of well-known prognostic significance. However, having in mind the limited number of cases studied, as well as a lower sensitivity of in situ hybridization technique, an analysis of larger series, as well as introducing a more sensitive technique like PCR assay, will be necessary to determine whether the presence of HPV DNA and HPV type should be considered when developing treatment strategies and assessing prognosis in patients with early stage cervical carcinomas.
Keywords: uterine cervix; invsive carcinoma; human papillomavirus; in situ hybridization; prognostic factors; recurrence